Perancangan Sistem Informasi Tempat Ibadah Beragam Agama Di Kota Solo - Novitasari, Anindya Difa, Hernawan Sulistyanto, S.T.,M.T (2017)
Information about worship place in Solo is needed in order to find the information of worship place for the people outside of Solo or people from Solo. Need to be made a web-based information system that displays and contains religious information of worship place in Solo, especially : Mosque, Church, Temple, Shrine and Kelenteng. The website uses programming language PHP and database MySQL. The method applied in this information system is Waterfall method and tested by conducting a questionnaire to 30 respondents to run the systems and the percentage result is 89% of respondents stated that the website is easy to use and the text easy to read and understand. The final result of the system of this website allows people outside or inside Solo city to looking for a place of worship place, information of worship place and to-do routine from each worship place to be more easily, quickly and efficiently.